Modelling and estimation of HIV prevalence and number of people living with HIV in India, 2010–2011. (December 2016) - Raj, Yujwal; Sahu, Damodar; Pandey, Arvind; Venkatesh, S; Reddy, DCS; Bakkali, Taoufik; Das, Chinmoyee; Singh, Kh Jitenkumar; Kant, Shashi; Bhattacharya, M; Stover, John; Jha, Ugra Mohan; et al.
This paper provides HIV estimation methodology used in India and key HIV estimates for 2010–2011. We used a modified version of the Spectrum tool that included an Estimation and Projection Package as part of its AIDS Impact Module. Inputs related to population size, age-specific pattern of fertility, gender-ratio at birth, age and gender-specific pattern of mortality, and volume and age–gender distribution of net migration were derived from census records, the Sample Registration System and large-scale demographic health surveys. Epidemiological and programmatic data were derived from HIV sentinel surveillance, large-scale epidemiological surveys and the programme management information system. Estimated adult HIV prevalence retained a declining trend in India, following its peak in 2002 at a level of 0.41% (within bounds 0.35–0.47%). By 2010 and 2011, it levelled at estimates of 0.28% (0.24–0.34%) and 0.27% (0.22–0.33%), respectively. The estimated number of people living with HIV (PLHIV) reduced by 8% between 2007 and 2011. While children accounted for approximately 6.3% of total HIV infections in 2007, this proportion increased to about 7% in 2011. With changing priorities and epidemic patterns, the programme has to customise its strategies to effectively address the emerging vulnerabilities and adapt them to suit the requirements of different geographical regions.